(untitled) (Journal of natural sciences, life and applied sciences, 2025)
Table of Content: • Pollution In The Lagoons of Central-West Jeddah City Ms. Sara Husain Alghamdi, Asst-Prof. Abrar Abdulhadi Almalki • Evaluation of the Immunological Markers IL-10 and IL-12 in Patients with Systemic Lupus Erythematous Lecturer / Ali Mohammed Abd-Alameer • Transcending Rational Principles: Mathematical Infinity as a Foundation for New Principles – Four Absolute Binary Theorems as a Basis for Absolute Infinite Systems Dr. Abdelrahman Yousif Bashclare